“Can You Deny Her That?” Processes of Governmentality and Socialization of Parents in Elite Women’s Gymnastics - Smits, Froukje; Jacobs, Frank; Knoppers, Annelies (Frontiers in Psychology, 2022)
Abusive practices in elite women’s artistic gymnastics (WAG) have been the focus of discussions about how to eliminate or reduce them. Both coaches and parents have been named as key actors in bringing about change. Our focus is on parents and their ability to safeguard their daughters in WAG. Parents are not independent actors however, but are part of a larger web consisting of an entanglement of emotions and technologies and rationalities used by staff, other parents, and athletes, bounded by skill development plans and by coaching expertise and authority. This entanglement may limit the ability of parents to bring about change. We draw on the Foucauldian concept of governmentality and Ahmed’s notion of entanglement of discourses and emotions to explore how parents are disciplined into accepting dominant discursive practices. The data were drawn from a project called the Parental Awareness Program (PAP). The purpose of PAP was to make parents aware of practices in competitive WAG that may not be in their child’s best interest. Participants were parents of young gymnasts who had been identified as ‘talented’ and who were members of an elite gymnastics club. The data analysis was based on four focus group discussions with 22 parents and semi-structured interviews with 8 parents. The results suggest that although parents problematized many practices during PAP, processes of governmentality involving discourses about coaching expertise, families, talent, enjoyment, long term skill development plans and its associated time demands, together ensured parental consent for dominant practices. The data suggested that a reduction of abusive practices lies in part in critical examinations of skill development plans that are presented as regimes of truth and are kept in place by emotions and the authority accorded to coaching expertise. These processes curtail parents in their ability to safeguard what is in the best pedagogical interest of their daughter.